Coastline, Mackenzie Delta 1972 - 2007, Beaufort Sea, northern Canada - Hynes, Sheila; Solomon, Steve; Whalen, Dustin (Canadian Cryospheric Information Network, 2015)
The following dataset represents coastlines as they existed along the Mackenzie Delta front, Richard island and Tuktoyaktuk Peninsula of the Beaufort Sea since 1972. These features provide an accurate representation of the land/water interface at a given time and position along the coastline. Aerial photography provided by National Airphoto Library (NAPL) and satellite imagery (Quickbird) provided the base layer for the dataset. TDigital coastlines, cliff lines and beach crests were generated from the accurately georeferenced aerial photography. The cliff depicted in the aerial photography was digitized as a line and saved as a vector file for each year that the base data was available. For more information please refer to the datafiles entitled: CCIN12048_20150121_Mackenzie_Delta_coastline_YEAR_Extended_Metadata_FGDC.xml : Purpose: The comparison of digital coastlines across various time intervals allows for an accurate representation of coastal change. A better understanding of coastal change and its relationship to the changing morphology of coastal and inland waterways will aid in future decision-making for development and management of one of the most rapidly changing coastlines in the world. : Summary: Not Applicable